2013
DOI: 10.1016/j.jad.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Activity monitoring in patients with depression: A systematic review

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
185
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(216 citation statements)
references
References 40 publications
26
185
4
1
Order By: Relevance
“…A majority of these features indicate that enhanced physical activity and more movement outside of your house are observed when the participant scores lower on the depression scale. This is in consistency with the Actigraph systematic review papers by Scott et al [28] who revealed a consensus of lower mean activity levels in bipolar depression, and Burton et al [29] that revealed a pattern of lower daytime activity but higher night time activity in depression. Entropy is the most prominent feature in the figure with many studies (n = 6), all yielding a negative correlation and a high statistical significant proportion.…”
Section: Secondary Featuressupporting
confidence: 89%
See 2 more Smart Citations
“…A majority of these features indicate that enhanced physical activity and more movement outside of your house are observed when the participant scores lower on the depression scale. This is in consistency with the Actigraph systematic review papers by Scott et al [28] who revealed a consensus of lower mean activity levels in bipolar depression, and Burton et al [29] that revealed a pattern of lower daytime activity but higher night time activity in depression. Entropy is the most prominent feature in the figure with many studies (n = 6), all yielding a negative correlation and a high statistical significant proportion.…”
Section: Secondary Featuressupporting
confidence: 89%
“…Together with a small number of total participants, the two features were weakly represented in the literature. Activity was on wD = -1 for the non-clinical samples of participants which was in accordance to the systematic review study on activity from Actigraph devices that found a clear pattern of less activity in patients with depression [29].…”
Section: Clinical Samples Of Patients Diagnosed With Ud or Bdsupporting
confidence: 87%
See 1 more Smart Citation
“…Depression, a mental disorder with a high incidence, has been clinically characterized by mental retardation, anhedonia, a lack of energy and numerous other physical symptoms (1). Depression brings severe stress and places a burden on the patients themselves, their families and society as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Twenty-four-hour motor activity in the depressed state seems to be lower than in the euthymic state. 8,[21][22][23] Previous studies have failed to find correlations between total scores in depression rating scales and actigraphic daytime activity, [24][25][26][27] and it has been suggested that motor retardation may be better assessed by specific retardation scales.…”
mentioning
confidence: 99%